Urinary tract infection and its association with the use of bladder catheter, diabetes and prostration - Minaya-Escolástico, Luis Oscar (2018)
Introduction: The aim of the present study was to determine the inpatient urinary tract infections frequency and its association with bladder catheter use, diabetes and prostration. Methods: It was carried out a prevalence descriptive cross-sectional study in tract urinary infection diagnosed patients during hospitalization at ESSALUD-Huánuco Hospital II, from January to October 2015. The sampling was for convenience, patients with abnormal urine analysis results, urine culture and antibiogram was chosen. Results: It was found an inpatient urinary tract infections frequency of 110 cases. Average age of 45 with standard deviation of+/- 19,6 years old. Females were more affected (66,4%). Statistical significance was found between bladder catheter use and diabetes, but not for prostration. The more frequent germs were E.coli (42,7%), Klebsiella (17,3%) and Proteus (16,4%). It was found that E.coli was Ceftriaxone and Ampicilin resistant. Conclusions: There is association between inpatient urinary tract infection, longtime bladder catheter use and diabetes diagnose. The more frequent isolated germs were E.coli, Klebsiella and Proteus.